Analisis Kualitas Pelayanan Perpustakaan Universitas Negeri Gorontalo Dengan Metode Importance Performance Analyse - Wunarlan, Irwan; Wolok, Eduart (Jurnal Entropi, 2009)
The Library of university existence was need and desire requirement of consumer society information. But, often happened library which we have not yet fulfill requirement of consumer information, consumer was not satisfied with given service by library, either from collection facet, staff attitude which do not care with care with consumer or system exist in library disagree with consumer expectation. Target in this research will knowing the quality of given service by library of Gorontalo State University toward student customer related to preparation of BLU implementation and specified minimum service at library university . Technique Intake of sample used proportional random sampling. Amount of sample are 100. The data from spreading of questionnaire used tabulation, after then it used Importance-Performance Analyze. Values based measure indicator satisfaction of consumer was compared with difference criterion of quality and the values included into Importance Performance matrix. Based to research, as a whole dimension of quality of service Gorontalo State University library was not quality and it was dissatisfactory and Gorontalo State University library was under mark specified minimum service by PPK BLU UNG and standard of university library